Cytomegalovirus mismatch after heart transplantation: Impact of antiviral prophylaxis and intravenous hyperimmune globulin. Issue 4 (15th September 2021) - Immohr, Moritz B.; Akhyari, Payam; Böttger, Charlotte; Mehdiani, Arash; Dalyanoglu, Hannan; Westenfeld, Ralf; Oehler, Daniel; Tudorache, Igor; Aubin, Hug; Lichtenberg, Artur; Boeken, Udo
Abstract: Objective: Cytomegalovirus (CMV) infections are correlated with complications following heart transplantation (HTx) and impaired outcome. The impact of a serologic mismatch between donor and recipient and the necessity of prophylactic virostatic medication is still a matter of concern. Methods: We retrospectively reviewed all patients that underwent HTx between 2010 and 2020 in our department. The recipients ( n  = 176) could be categorized into four risk groups depending on their serologic CMV matching (D + /R −  = donor CMV‐IgG positive and recipient CMV‐IgG negative, n  = 32; D − /R +, n  = 51; D − /R −, n  = 35; D + /R +, n  = 58). All patients followed the same protocol of CMV prophylaxis with application of ganciclovir/valganciclovir and intravenous CMV hyperimmune globulin. RESULTS: Incidence of postoperative morbidity such as primary graft dysfunction, neurological events, infections, and graft rejection were comparable between all groups ( p  > .05). However, the incidence of postoperative acute kidney injury with hemodialysis was by trend increased in the D − /R + group (72.0%) compared to the other groups. In‐hospital CMV‐DNAemia was observed in serologic positive recipients only (D + /R − : 0.0%, D − /R + : 25.0%, D − /R − : 0.0%, D + /R + : 13.3%, p  < .01). During the first year, a total of 18 patients developed CMV‐DNAemia (D + /R − : 31.6%, D − /R + : 31.9%, D − /R − : 3.4%, D + /R + : 11.1%, p  = .03). Conclusions: Seropositive recipients carry an important risk for CMV‐DNAemia. However, we did not observe differences in perioperative morbidity and mortality regarding CMV matching, which might be related to regularly administer prophylactic virostatics and additional CMV‐IVIG for risk constellations. For high‐risk constellation, long‐term application of CMV‐IVIG during the first year after transplant may be beneficial. Abstract : Seropositive recipients carry an important risk for CMV‐DNAemia. However, we did not observe differences in perioperative morbidity and mortality regarding CMV matching, which might be related to regularly administer prophylactic virostatics and additional CMV‐IVIG for risk constellations. For high‐risk constellation, long‐term application of CMV‐IVIG during the first year after transplant may be beneficial.